2019
DOI: 10.1042/ns20180206
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral state-dependent lateralization of dorsal dentate gyrus c-Fos expression in mice

Abstract: Hemispheric lateralization is a fundamental organizing principle of nervous systems across taxonomic groups with bilateral symmetry. The mammalian hippocampus is lateralized anatomically, physiologically, and chemically; however, functional asymmetries are not yet well understood. Imaging studies in humans have implicated the left and right hippocampus in specialized processing. However, it is not clear if lateralized activity occurs in the rodent hippocampus. c-Fos imaging in animals provides a measure of neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Neurons in the dentate gyrus, two synapses upstream of the CA1, have been implicated in pattern separation processes that may be necessary for contextual behaviour 43 and can do so through differences in millisecond-timescale coactivity 25 . Moreover, there is evidence for a left dominance in the expression of the activity marker cFos in the dentate gyrus during novel object exploration 44 . Importantly, while CA3 neurons in one hemisphere send commissural projections to the contralateral hemisphere 33 , the two hemispheres seem to retain functional differences in their projections to CA1 35 , 42 which we target directly.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in the dentate gyrus, two synapses upstream of the CA1, have been implicated in pattern separation processes that may be necessary for contextual behaviour 43 and can do so through differences in millisecond-timescale coactivity 25 . Moreover, there is evidence for a left dominance in the expression of the activity marker cFos in the dentate gyrus during novel object exploration 44 . Importantly, while CA3 neurons in one hemisphere send commissural projections to the contralateral hemisphere 33 , the two hemispheres seem to retain functional differences in their projections to CA1 35 , 42 which we target directly.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, if there is indeed a relationship between embryonic organization of organ laterality and hippocampal laterality (Goto et al, 2010;Kawakami et al, 2008), consistent organ laterality across sexes would indicate that consistent development of hippocampal laterality across sexes is likely. One study found no difference between adult males and female mice in left or right hippocampal c-Fos expression or in degree of lateralization (Jordan et al, 2019). While there is no data to suggest that hippocampal lateralization in males and females may be different, future studies will have to include females to determine whether or not an additional framework is needed (Shansky, 2019).…”
Section: Does Lateralization Differ Across Sexes?mentioning
confidence: 99%
“…These asymmetries were only recently uncovered using advanced methods. Importantly, a recent study showed that failure to consider differences between the left and right rodent hippocampi in cellular quantification experiments can lead to incomplete and inconsistent conclusions (Jordan, Shanley, & Pytte, 2019). Collectively, these findings indicate the importance of understanding the hippocampus as a bilateral structure and of taking into account differences across hemispheres.…”
mentioning
confidence: 99%
“…In fact, if there is indeed a relationship between embryonic organization of organ laterality and hippocampal laterality (Kawakami et al, 2008;Goto et al, 2010), consistent organ laterality across sexes would indicate that consistent development of hippocampal laterality across sexes is likely. One study found no difference between adult males and female mice in left or right hippocampal c-Fos expression or in degree of lateralization (Jordan et al, 2019). While there is no data to suggest that hippocampal lateralization in males and females may be different, future studies will have to include females to determine whether or not an additional framework is needed (Shansky, 2019).…”
Section: Does Lateralization Differ Across Sexes? a Majority Of Rodenmentioning
confidence: 99%
“…These asymmetries were only recently uncovered using advanced methods. Importantly, a recent study showed that failure to consider differences between the left and right rodent hippocampi in cellular quantification experiments can lead to incomplete and inconsistent conclusions (Jordan et al, 2019). Collectively, these findings indicate the importance of understanding the hippocampus as a bilateral structure and of taking into account differences across hemispheres.…”
Section: Introductionmentioning
confidence: 99%